2017
DOI: 10.3389/fenvs.2017.00037
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Disintegration Process in Anaerobic Digestion of Tannery Sludge and Fleshing

Abstract: Mathematical modeling of anaerobic digestion (AD) is widely acknowledged as a powerful tool to v of the process and to support full-scale plant design, operation and optimization. In this work, a modified version of the IWA-ADM1 model is proposed to simulate the AD of tannery primary sludge (TPS) and fleshing, with special emphasis on the disintegration formulation. Multiple batch tests were performed at different inoculum/substrate VS-mass ratio, in order to evaluate the biodegradability of the two substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…While a very high ISR will primarily challenge the experimental setup due to the relatively low gas production of the substrate (Caillet et al, 2019), a low ISR could cause an overload of the microbial community, as has already been shown in several studies. previous (Polizzi et al, 2017;Holliger et al, 2016). From the literature consulted, it can be concluded that methane production rates are specific to the substrate and the inoculum, so it is not always possible to make general statements about the performance of digestion.…”
Section: Effect Of Isr On Biomethane Potential and Biodigester Stabilitymentioning
confidence: 80%
“…While a very high ISR will primarily challenge the experimental setup due to the relatively low gas production of the substrate (Caillet et al, 2019), a low ISR could cause an overload of the microbial community, as has already been shown in several studies. previous (Polizzi et al, 2017;Holliger et al, 2016). From the literature consulted, it can be concluded that methane production rates are specific to the substrate and the inoculum, so it is not always possible to make general statements about the performance of digestion.…”
Section: Effect Of Isr On Biomethane Potential and Biodigester Stabilitymentioning
confidence: 80%
“…The most common flaw in BMP test is overloading which can be caused by either low inoculum intrinsic activity or by a low ISR. While a very high ISR will mainly challenge the experimental setup due to the relatively little gas production from the substrate, a low ISR might cause overloading of the microbial community, as has been demonstrated in various previous studies already (Hashimoto, 1989;Raposo et al, 2006;Kafle et al, 2014;Polizzi et al, 2017). Still, the impact of ISR on the shape of SMP curve has not been reported so far.…”
Section: Impact Of Inoculum-to-substrate Ratio (Isr) On Smp Curvesmentioning
confidence: 94%
“…The non-degradable fractions are soluble and non-soluble inert particulates, whereas the degradable fractions consist of biopolymers, in ADM1 (Anaerobic Digestion Model No. 1) limited to polysaccharides, proteins, and lipids [49][50][51]. Disintegration is mostly described by first-order kinetics, sometimes assumed to be part of the hydrolysis step.…”
Section: Disintegration Of Solid Particulatesmentioning
confidence: 99%